Ketotic hypoglycemia in patients with Down syndrome. Issue 1 (28th July 2021) - Drachmann, Danielle; Carrigg, Austin; Weinstein, David A.; Petersen, Jacob Sten; Christesen, Henrik Thybo
ABSTRACT: Background: Ketotic hypoglycemia (KH) without an identifiable underlying metabolic or hormonal disease is historically named idiopathic KH. The prevalence is unknown, but idiopathic KH is considered the most frequent cause of hypoglycemia beyond the neonatal period. KH in Down syndrome (DS) has not been reported. Methods: We conducted a web‐based survey on KH in DS through the non‐profit patient organization Ketotic Hypoglycemia International. The responses were evaluated for consistency with KH by two authors. Two DS patient histories with documented KH were shared in more details. Results: Survey data on 139 DS patients were obtained. After validation, 10 patients (7.2%) had reported episodes of documented hypoglycemia, ketosis, and/or symptoms compatible with KH beyond the neonatal period. Glucose concentrations ranged 1.2‐2.9 mmol/L; betahydroxybutyrate was up to 5.5 mmol/L during hypoglycemia. One girl had trisomy 21 with no response to i.m. glucagon also had a heterozygous Xp22.23 deletion including GYG2, which protein, glycogenin 2, is a substrate for glycogen synthase. Treatment with extended release cornstarch was effective. Conclusion: This is the first demonstration of a possible high prevalence of KH in DS. Even though this finding needs to be confirmed in other research settings, identification of KH in DS could have a dramatic impact, as simple treatments with cornstarch, protein and frequent meals may prevent KH attacks and, analogous to other conditions with KH, improve growth, stamina and prevent overeating and obesity. GYG2 deletion may contribute to KH in DS, resembling glycogen storage disease type 0.